RISK MANAGEMENT AND MSME ACCOUNTING PRACTICES: AN EXPLORATORY REVIEW OF PRACTICES IN INDONESIA AND MALAYSIA - Edward , Oswald Timothy; Mukti, Aloysius Harry (Jurnal Penelitian Akuntansi (JPA), 2025)
This study explores the integration between risk management and accounting practices among Micro, Small, and Medium Enterprises (MSMEs) in Indonesia and Malaysia. Despite increasing attention on MSME resilience, small business actors often treat accounting and risk management as separate functions. Through a qualitative exploratory review of academic literature, institutional reports, and policy documents, this research identifies three critical issues: (1) limited risk awareness, (2) informal and compliance-driven accounting systems, and (3) the lack of strategic linkage between financial data and risk-based decision-making. Macroeconomic data from Bank Negara Malaysia were incorporated to contextualize the findings, showing that while institutional and financial stability is relatively strong, enterprise-level integration remains fragmented. The study highlights the need for a more coherent and integrated approach where financial literacy, risk awareness, and decision-making capacity are treated as interconnected domains. Strengthening MSME resilience requires not only institutional support but also internal transformation in how accounting information is interpreted and applied for risk mitigation.